Twenty Years of Japanese Electroacoustic Music: Trends in 1990s and JSEM. - Mizuno, Mikako (Contemporary Music Review)
This paper surveys the general trends of Japanese electroacoustic music since 1990 and describes the history of Japanese Society of Electronic Music (JSEM), the JSEM which was founded in 1992 and describes not only the activities and the conceptual background of the society but also some the technical changes that influenced composers' artistic vision. The JSEM is a social group for Japanese composers and musicologists whose aim is to activate communication and research with the common thought of creating new electronic music. JSEM is now composed of 40 members, most of whom are composers. JSEM has several concerts each year besides their annual concerts.